"Heal Your Messenger, Kirdgoro..." - Nazzora Bekzoda; Parvina Qazokova Uygun Qizi (Genius Journals, 2023)
Allah is the possessor of incomparable and incomparable power. The names and attributes of Allah are praised in a unique way in the Eastern classical literature. Hazrat Nawai did not limit himself by starting each work with praise, but started each series of letters with praise. In this article, the analysis and meanings of the 5th ghazal from Alisher Navoi's work "Garayib us sigar" are revealed.
Keywords: Tanzi ul-mulk; Nimrud; Tajalli; Iskandar